2021
DOI: 10.1007/s10903-021-01146-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Physical Health Outcomes of Resettled Refugee Populations in the United States: A Scoping Review

Abstract: Several studies describe the health of recently resettled refugee populations in the US beyond the first 8 months after arrival. This review summarizes the results of these studies. Scientific articles from five databases published from January 2008 to March 2019 were reviewed. Articles were included if study subjects included any of the top five US resettlement populations during 2008–2018 and if data described long-term physical health outcomes beyond the first 8 months after arrival in the US. Thirty-three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 48 publications
1
32
1
Order By: Relevance
“…Repeatedly and uniformly, studies show a high risk of mental health burdens among refugee women, including symptoms of posttraumatic stress and depression [13][14][15][16][17]. Refugees also show a high prevalence of various serious non-communicable and communicable diseases, including diabetes, hypertension, and HIV [17][18][19][20]. Obstetric complications are also common, with higher rates of maternal and neonatal morbidity among forced migrants compared with non-migrant populations [17,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Repeatedly and uniformly, studies show a high risk of mental health burdens among refugee women, including symptoms of posttraumatic stress and depression [13][14][15][16][17]. Refugees also show a high prevalence of various serious non-communicable and communicable diseases, including diabetes, hypertension, and HIV [17][18][19][20]. Obstetric complications are also common, with higher rates of maternal and neonatal morbidity among forced migrants compared with non-migrant populations [17,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…One study has found that LEP patients with language-discordant physicians were more likely than LEP patients with language-concordant physicians to have poor glycemic control. 7 Thus, outcomes were improved for LEP patients when the patient and provider can communicate more easily. Our data supported this finding given that the observed differences among language groups dissipated after stratifying patients by language concordance with their providers.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Even when compared to their U.S.-born ethnic counterparts, refugees have higher rates of diabetes. 6 , 7 Health education promoting physical activity and optimal self-care for LEP patients with Type 2 diabetes mellitus (T2DM) in primary care settings is often ineffective, leading to poorer control of blood glucose and poorer health outcomes than among English-speaking patients. 8 Other significant barriers to effective management of chronic disease, including diabetes mellitus, in refugees with LEP include: varying cultural beliefs about illness, 2 ineffective communication between provider and patient, 9 decreased access to pharmacy and medication services, 10 and decreased health literacy.…”
Section: Introductionmentioning
confidence: 99%
“…According to the United Nations high Commissioner for Refugees (UNCHR) 79,5 million people around the world had been forcibly displaced from their primary residence at the end of 2019, including 26 million refugees. Refugees are constantly faced with multiple acute and chronic illnesses (14). Among them, a particularly sensitive group are women in pregnancy (15).…”
Section: Discussionmentioning
confidence: 99%